Educación física en la educación infantil Una propuesta y algunas experiencias - LOPEZ PASTOR, Víctor M. coord. (MIÑO Y DAVILA, 2004)
Colaboradores: ABAD, Mavela; GIL, Beatriz Aldama; ALONSO LOZANO, Alvaro; AMOROS, Virginia; ANTON MIÑAMBRES, María Ascención; ROMERO, Yolanda Consuegra; GARCIA DE LA PUENTE, José Manuel; GOMEZ MARTIN, Sara; SANDIN, Roberto Hidalgo; LUMBRERAS, Irene Llorente; MIGUEL ARROYA, Angela; PALOMO MARTIN, Helena; PEDRAZA GONZALEZ, Miguel; SANCHO COCO, Beatriz; SANTOS MARCOS, Judith; VAZQUEZ SANTAMARIA, Laura; VICENTE OLMOS, Sara de